Biochemistry - Blackstock, James C. ([S.l.] : Hodder Education Publishers, 1998)
This Biochemistry volume covers what is a key topic for many biomedical disciplines focusing on the basic principles and reflecting the most recent advances in human and mammalian biochemistry. It provides an up to date synopsis which will form a basis from which to study related topics, or to study biochemistry at a more advanced level.
Keywords: biochemistry